DIPLOMASI KOERSIF AMERIKA SERIKAT TERHADAP IRAN PASCA MUNDUR DARI JOINT COMPREHENSIVE PLAN OF ACTION (JCPOA) TAHUN 2018 - Rud Calara Cintia Simanjuntak; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research analyzes how the United States' foreign policy in the Trump regime, regarding its coercive diplomacy towards Iran through the application of sanctions after the withdrawal from the JCPOA multilateral agreement. The American decision was taken when Iran was still complying with the terms of the JCPOA agreement. Through this paper, the author explains that the reason for the United States' withdrawal from the JCPOA agreement was basically due to the non-realization of America's interests towards Iran in the agreement, so to achieve this interest, the United States pressured Iran in the form of coercive diplomacy.This research was completed through qualitative methods and descriptive analysis. with data collection techniques through literature study sourced from several books, journals, articles, and websites. This study uses the realism perspective and the theory of coercive diplomacy developed by Tom Suer, which the author develops into five main variables, namely goals, demands, threats, time pressure, and motivation.The results is  indicate that the coercive diplomatic policy implemented by the United States has so far not been effective in achieving its goals, even though American sanctions have succeeded in suppressing the Iranian economy. The ineffectiveness of the sanctions can be seen from Iran's response, which is still continuing to enrich uranium. Keywords: JCPOA, Coercive Diplomacy, United States - Iran.